2009
DOI: 10.1080/09064710801932425
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2concentration alleviates salinity stress in tomato plant

Abstract: Tomato [Solanum lycopersicum (formerly Lycopersicon esculentum) L. cv. Momotarou] plants were grown under potted conditions inside the greenhouse of Hiroshima University, Japan. The effects of salinity stress under either ambient or elevated CO 2 atmospheric conditions during the fruit-growth period were compared. Stem was the major sink organ for the carbon assimilates from the source leaves. A simple nondestructive micromorphometric technique was used to measure growth of these organs. The effect of salt str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(31 reference statements)
1
4
0
1
Order By: Relevance
“…S1 ). These findings agree with those of other studies concerning the relationships between elevated CO 2 levels and high salinity in tomato and other plant species Takagi et al , 2009 ; ( Del Amor, 2013 ; Zaghdoud et al , 2013 ; Pinero et al , 2014 ; Yu et al , 2015 ). High CO 2 levels decreased leaf transpiration rates and stomatal conductance values, even in plants grown with high salt ( Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S1 ). These findings agree with those of other studies concerning the relationships between elevated CO 2 levels and high salinity in tomato and other plant species Takagi et al , 2009 ; ( Del Amor, 2013 ; Zaghdoud et al , 2013 ; Pinero et al , 2014 ; Yu et al , 2015 ). High CO 2 levels decreased leaf transpiration rates and stomatal conductance values, even in plants grown with high salt ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to increasing photosynthetic CO 2 assimilation rates, growth with high atmospheric CO 2 levels can mitigate against the negative impacts of abiotic stresses ( Ameye et al , 2012 ; Bauweraerts et al , 2013 ; Zinta et al , 2014 ). For example, growth under high CO 2 led to enhanced tolerance to salinity, Fe deficiency and increased resistance to (hemi) biotrophic microbes such as tobacco mosaic virus and Pseudomonas syringae in tomato ( Solanum lycopersicum ; Jin et al , 2009 ; Takagi et al , 2009 ; Del Amor, 2013 ; Li et al , 2015 ). In contrast, growth under elevated CO 2 enhanced susceptibility to the necrotrophic pathogen, Botrytis cinerea ( Zhang et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in photosynthesis under higher CO 2 was due to reduced source activity by partial defoliation, whereas in intact plants the increase in CO 2 increased source activity and photosynthesis remains unchanged. Takagi et al (2009) have shown that net photosynthesis of the defoliated plant increased by elevated CO 2 (100 Pa) by about 35% relative to that in the ambient air and down regulation was not observed during the 14-day experimental period in tomato (Lycopersicum esculentum L.). Plants may respond positively to moderate defoliation under elevated CO 2 , but responsiveness decreases with high frequency of defoliation (Wand and Midgley 2004).…”
Section: Significance Of Defoliation Under Stressmentioning
confidence: 97%
“…As temperaturas consideradas moderadamente altas (35 a 42°C) podem causar danos diretos à fotossíntese (Wise et al, 2004), por provocarem mudanças na membrana do tilacóide e alterarem as propriedades físico-químicas e também a organização funcional dessas estruturas celulares (Streit et al, 2005). Em elevadas temperaturas, a taxa máxima de assimilação de carbono pode ser inibida por diminuir a condutância estomática (Takagi et al, 2009). Além disso, altas temperaturas podem levar ao aumento da respiração mitocondrial e da fotorespiração.…”
Section: Resultsunclassified